التشحين العنفي في محركات الديزل البحرية الكبيرة ثنائية الأشواط - حمود بسام (Latakia University Journal -Engineering Sciences Series, 2019)
يعد تطوير جمل التشحين أحد أهم شروط تحسين أداء محركات الديزل البحرية ثنائية الأشواط التي تكون عادةً ذات حجوم كبيرة وتقوم بدفع معظم السفن التجارية في العالم. يتناول هذا البحث التقانات المستخدمة في الوقت الحاضر لتطوير محركات السفن من خلال التشحين ويركز على نسبة انضغاط الشاحن ومردوده باعتبارهما البارامترين الأساسيين في تحسين أداء محركات الديزل البحرية ثنائية الأشواط ورفع مردودها. ولمراعاة المتطلبات المستقبلية من جهة التشحين فإن البحث يعرض التقانات التي هي قيد الدراسة في مراكز التطوير والبحث مثل التحكم بزاوية دخول الغازات إلى العنفة الغازية، والتشحين ثنائي المراحل، وتدوير غازات الاحتراق، وأجهزة التشحين باستخدام مصدر مساعد للقدرة. Turbo-charging is very important for further performance development of large two-stroke diesel Engines which power the majority of ships. This paper deals with the state of current technology in terms of turbochargers and their interaction with these large engines. Pressure ratio and turbocharger efficiency are the key parameters for further development of large two-stroke engine performance. This paper also looks forward to future requirements of turbo-charging systems and comments on concepts such as variable turbine geometry, two-stage turbo-charging, internal exhaust gas recirculation, and turbochargers with auxiliary drives that have been proposed or are being developed for future application.